KERAPUHAN EVIDENSI DALAM CIVIC LITERACY - Andri Fransiskus Gultom (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2022)
The debate about civic literacy in philosophical discourse in Indonesia is still rare. This paper may have initiated this debate by anchoring philosophical criticism to the research of Armaidy Armawi and Raharjo in the Journal of Philosophy Vol 31, No. 1 of 2021 entitled: